Pengaruh Brand Awareness dan Kualitas Produk Terhadap Keputusan Pembelian Produk HPL Skylam (Studi Kasus pada Konsumen PT. Anugrah Cipta Interindo) - Vira Agustina (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
This research was aimed to know the effect brand awareness and product quality towards a purchase decision in PT. Anugrah Cipta Interindo (A Case Study in consumer PT. Anugrah Cipta Interindo). This type of research was quantitative research. The population in this research were consumer PT. Anugrah Cipta Interindo. The sample was determined by saturated sampling and obtained 40 respondents as a sample. The results showed that: (1) Brand Awareness has a positive and significant effect towards a Purchase Decision (2) Product Quality has a positive and significant effect towards a Purchase Decision (3) Brand Awareness and Product Quality have a simultaneous effect towards a Purchase Decision. Keywords: Brand Awareness; Product Quality; Purchase Decision